Call Timing of Callable Non-Convertible Bonds: A Survival Analysis - Wee, Jung Bum; Ryu, Keunkwan; Binh, Ki Beom (Journal of Reviews on Global Economics, 2018)
We empirically analyze the factors affecting corporate decisions to call non-convertible bonds using survival analysis. The results show that firms tend to defer calling non-convertible bonds in order to mitigate agency costs of debt (including under-investment and risk-shift); that calling is significantly more intense if positive information is revealed; that non-refundability clauses are binding on call decisions; that firms are more likely to redeem bonds to refund if market interest rates fall dramatically; and that this interest effect is stronger as the transaction costs of refunding decrease. Also, this paper shows that call intensity monotonically decreases after call protection periods expire.